Functional and structural balances of homologous sensorimotor regions in multiple sclerosis fatigue. Issue 3 (March 2016) - Dezza, I. Cogliati; Zito, G.; Tomasevic, L.; Filippi, M.M.; Ghazaryan, A.; Porcaro, C.; Squitti, R.; Ventriglia, M.; Lupoi, D.; Tecchio, F.
Abstract : Objective: Fatigue in Multiple Sclerosis (MS) is a highly disabling symptom affecting social relationships and daily cognitive and physical activities of patients, being complained by up to 90% of MS sufferers. Among the central mechanisms behind it, an involvement of sensorimotor networks is evident from structural and functional studies. We aimed at assessing whether functional/structural balances of homologous sensorimotor regions – known to be crucial for sensorimotor networks effectiveness – decrease with MS fatigue increase. Methods: Functional connectivity measures at rest and during a simple motor task (weak handgrip of either the right or left hand) were derived from primary sensorimotor areas EEG recordings in twenty-seven mildly disabled MS patients. Structural MRI-derived inter-hemispheric asymmetries included the cortical thickness of Rolandic regions and the volume of thalami. Results: Fatigue symptoms increased together with the functional inter-hemispheric imbalance of sensorimotor homologous areas activities at rest and during movement, in absence of any appreciable parenchymal asymmetries. Conclusion: People with MS suffering of chronic fatigue have higher left (dominant) than right hemispheric primary sensorimotor activity power in the resting state, without structural asymmetries. Key message: This finding supports the development of compensative interventions that may revert these neuronal activity imbalances to relieve fatigue in MS.